GFAP serves as a structural element of tunneling nanotubes between glioblastoma cells and could play a role in the intercellular transfer of mitochondria - Simone, L.; Capobianco, D. L.; Di Palma, F.; Binda, E.; Legnani, F. G.; Vescovi, A. L.; Svelto, M.; Pisani, F. (Frontiers in Cell and Developmental Biology, 2023)
Tunneling nanotubes (TNTs) are long F-actin positive plasma membrane bridges connecting distant cells allowing the intercellular transfer of cellular cargoes and are found to be involved in glioblastoma (GBM) intercellular crosstalk. Glial fibrillary acid protein (GFAP) is a key intermediate filament protein of glial cells involved in the cytoskeleton remodelling and linked to GBM progression. Whether GFAP plays a role in TNTs structure and function in GBM is unknown. Here, analysing F-actin and GFAP localization by laser-scan confocal microscopy followed by 3D reconstruction (3D-LSCM) and mitochondria dynamic by live-cells time-lapse fluorescence microscopy, we show the presence of GFAP in TNTs containing functional mitochondria connecting distant human GBM cells. Taking advantage of super-resolution 3D-LSCM, we show the presence of GFAP-positive TNTs-like structures also in resected human GBM. Using H2O2 or pro-apoptotic toxin staurosporine (STS), we show that GFAP-positive TNTs strongly increase during oxidative stress and apoptosis in GBM cell line. Culturing GBM cells with STS-treated GBM cells, we show that STS triggers the formation of GFAP-positive TNTs between them. Finally, we provide evidence that mitochondria co-localise with GFAP at the tip of closed-ended GFAPpositive TNTs and inside receiving STS-GBM cells. Summarizing, here we found that GFAP is a structural component of TNTs generated by GBM cells, that GFAP-positive TNTs are upregulated in response to oxidative stress and proapoptotic stress and that GFAP interacts with mitochondria during the intercellular transfer. These findings contribute to elucidate the molecular structure of TNTs generated by GBM cells, highlighting the structural role of GFAP in TNTs and suggesting a functional role of this intermediate filament component in the intercellular mitochondria transfer between GBM cells in response to proapoptotic stimuli.